Teachers' understandings of the social and professional support needed to implement change in Qatar. Issue 1 (January 2022) - Karkouti, Ibrahim M.; Abu-Shawish, Reem Khalid; Romanowski, Michael H.
Abstract: Currently, Qatar is implementing an educational reform to enhance teaching and learning in public and private schools. The Qatar National School Accreditation significantly impacted Qatar's private schools, requiring teachers to implement various mandated educational changes. Using House (1981) types of social support, this qualitative, phenomenological study was designed to explore teachers' understandings regarding the social and professional support they need to implement educational change at an international school in Qatar. To help teachers engage in change, findings revealed that educational leaders need to heed teacher wellbeing during educational reform, educational change should be contextualized and tailored to the needs of teachers, and support should be offered to reduce teachers' stress and facilitate the change process. Recommendations for educational leaders trying to help teachers implement mandated educational change are provided in light of the derived findings. Abstract : Educational change; Social support; Teacher development; Teacher stress.